2015
DOI: 10.4028/www.scientific.net/amr.1092-1093.1529
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Drying Temperature on Performance of Soybean Protein-Isolate/Carboxymethyl Cellulose/Stearic Acid Composite Films

Abstract: Drying is important for the matrix formation of composite films. A low drying temperature guarantees the compact matrix, while a higher temperature strengthens the crosslinking of ingredients. A balance point of the compact matrix and higher crosslinking degree was the key to enhance the performance of a composite film. The temperature of 30, 60, 90, and 120 oC was used to dry the soybean protein-isolate/carboxymethyl cellulose/stearic acid composite films. When being dried at 90 oC, the tensile strength of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Therefore, up to date, a variety of physical, chemical, and enzymatic modifications , have been applied to lower the brittleness and water sensitivity of SPI, among which blending SPI with another polymer has been proved to be the most effective approach . Different natural and synthetic polymers, such as chitosan, , alginate, cellulose, gelatin, , casein, poly­(vinyl alcohol), , poly ε-caprolactone, , and poly­(lactic acid) , have up to now been used as the secondary components for SPI-based materials. Nevertheless, the modification with hydrophilic polymer does not present satisfied effects on the improvement of water resistance, and for the modification with hydrophobic polymers, their compatibility with SPI is still an important issue which needs to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, up to date, a variety of physical, chemical, and enzymatic modifications , have been applied to lower the brittleness and water sensitivity of SPI, among which blending SPI with another polymer has been proved to be the most effective approach . Different natural and synthetic polymers, such as chitosan, , alginate, cellulose, gelatin, , casein, poly­(vinyl alcohol), , poly ε-caprolactone, , and poly­(lactic acid) , have up to now been used as the secondary components for SPI-based materials. Nevertheless, the modification with hydrophilic polymer does not present satisfied effects on the improvement of water resistance, and for the modification with hydrophobic polymers, their compatibility with SPI is still an important issue which needs to be solved.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the microstructure of the chitosan films changed when the chitosan films were re-dried and crystallized. This indicated that neutralization had a much greater effect on the thickness of the chitosan films than the concentration of the film-forming solution [ 20 ]. For chitosan films before neutralization, the tensile strength increased from 37.6 ± 0.9 MPa to 60.5 ± 3.1 MPa with an increase in the concentration of the film-forming solution.…”
Section: Resultsmentioning
confidence: 99%